Mesolithic Cultures of Ustyurt and Kyzylkum - Berik Madreymov (Acta Universitatis Lodziensis: Folia Archaeologica)
The article explores the history of archaeological research on the Mesolithic sites of Ustyurt and Kizilkum and the potential for revising existing archaeological materials, as well as advancing the study of the Mesolithic period in Uzbekistan to a contemporary level.